Doing the möbius strip: The politics of the Bailey Review. (September 2013) - Duschinsky, Robbie; Barker, Meg
In media and policy discourses on sexualisation, there has been an apparent split. Some have constructed young women as innocent children, incapable of meaningful sexual and commercial choices; others have treated young women as neo-liberal adults, agentic and savvy choice-makers. We analyse how the Bailey Review on the Sexualisation and Commercialisation of Childhood (published by the UK Department of Education) attempts to manage the tensions associated with making both arguments at once. We theorise the split as 'doing the möbius strip', as both sides agree on the assumption that commercial and sexual choice is either present or absent for young women. In this way, they reframe the contradictions and inequalities that shape young women's behaviours as a problem of propriety and decency.